Evaluation of salivary total antioxidant capacity and total oxidant status in patients with rheumatoid arthritis and systemic lupus erythematosus - Mohadeseh Soltanian; Mohammad Hassan Kalantar Neyestanaki; Aida Mehdipour; Maryam Masoumi; Mohammad Aghaali; Ali Saleh; Mojtaba Hossein Nattaj (BMC Rheumatology)
Abstract Background Oxidative stress plays a critical role in the pathogenesis of autoimmune diseases, including rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Assessing total antioxidant capacity (TAC) and total oxidant status (TOS) in saliva offers a non-invasive method to evaluate oxidative stress and its relationship with disease severity. This study aimed to measure salivary TAC and TOS levels in RA and SLE patients and compare them with healthy controls. Methods A cross-sectional study was conducted involving 90 participants: 30 RA patients, 30 SLE patients, and 30 healthy controls. Saliva samples were collected and analyzed using specialized TAC and TOS assay kits. Disease severity was evaluated using the Disease Activity Score-28 (DAS-28) for RA and the SLE Disease Activity Index (SLEDAI-2 K) for SLE. Statistical analyses included ANOVA, post-hoc tests, and Pearson correlation coefficients. Results Results showed that RA and SLE patients had significantly higher oxidative stress compared to healthy controls, with lower TAC levels (RA: 298.88 ± 31.21 µM, SLE: 287.98 ± 38.07 µM, Control: 461.22 ± 158.22 µM, P < 0.001) and higher TOS levels (RA: 5.81 ± 1.28 µM, SLE: 5.80 ± 1.36 µM, Control: 3.49 ± 1.56 µM, P < 0.001). The TOS/TAC ratio was also significantly elevated in RA (1.95 ± 0.44) and SLE (2.05 ± 0.64) patients compared to controls (0.84 ± 0.44, P < 0.001). A positive correlation was observed between TOS levels and age (R = 0.256, P = 0.016), while no significant gender-based differences were detected. Conclusions RA and SLE patients exhibit significant oxidative imbalance, as indicated by altered salivary TAC and TOS levels. These findings highlight the potential role of oxidative stress in these autoimmune diseases.